Physiological Response to Dolops carvalhoi (Crustacea: Branchiura) Infection by Pacu, Piaractus mesopotamicus, Subjected to Short Cycles of Food Restriction and Refeeding - Takahashi, Leonardo S. [UNESP]; Biller-Takahashi, Jaqueline D. [UNESP]; Urbinati, Elisabeth C. [UNESP] (Wiley-Blackwell, 2014)
Feeding strategies that reduce feed and promote compensatory growth could be an interesting tool to reduce costs in the fish production. However, fish health must be monitored to evaluate if their physiological response to adverse conditions, such as parasite infection, does not become compromised. A 12-wk growth trial was conducted to determine the physiological responses of pacu, Piaractus mesopotamicus, that were subjected to different fasting/refeeding cycles and infected with the Dolops carvalhoi. The schemes were: (i) control group fish (FD), (ii) food-restricted and controlled refeeding group (FR/Rc), and (iii) food-restricted and refeeding to satiation group (FR/Rs). After 84 d, the fish were exposed to D. carvalhoi for 30 h. The fish subjected to food restriction did not exhibit compensatory growth. Cortisol levels decreased in all groups within 30 h after infection. Glucose levels increased 6 h after the D. carvalhoi in the FR/Rs and 30 h after infection in the FD. In all of the fish groups, the hematocrit values were reduced after infection, and it was associated with a reduction in the mean corpuscular volume and erythrocytes. At 30 h after infection, the number of erythroblasts increased. The use of the feeding schemes does not indicate a failure of the pacu physiological responses.